Ketepatan Perspektif Gender Pendidikan Islam: Studi Kritis Internalisasi di SMA Islam Temayang - Khaidar Muhammad Fu’ad Sayyidurrijal; Sri Minarti (CV. ITTC INDONESIA, 2026)
Islamic education has a strategic role in shaping students’ mindsets and characters, including their understanding of gender equality values. However, educational practices are still influenced by social constructions, patriarchal culture, and textual religious interpretations that lead to inaccuracies in gender perspectives. This study aims to analyze the accuracy of gender perspectives in Islamic education through a critical study of the internalization of gender values at SMA Islam Temayang. This research employed a qualitative approach with a critical case study design. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, and school policies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing based on social construction theory and justice-based Islamic education. The results show that the internalization of gender values has encouraged mutual respect between male and female students, although stereotypes of roles and gender-based activity divisions are still found. Islamic education therefore requires a contextual approach so that gender equality values can be realized concretely within school culture..